Intratumoral injection of a CpG oligonucleotide reverts resistance to PD-1 blockade by expanding multifunctional CD8⁺ T cells - Wang, Shu; Campos, Jose; Gallotta, Marilena; Gong, Mei; Crain, Chad; Naik, Edwina; Coffman, Robert L.; Guiducci, Cristiana (Proceedings of the National Academy of Sciences - PNAS, 2016)
Despite the impressive rates of clinical response to programmed death 1 (PD-1) blockade in multiple cancers, the majority of patients still fail to respond to this therapy. The CT26 tumor in mice showed similar heterogeneity, with most tumors unaffected by anti–PD-1. As in humans, response of CT26 to anti–PD-1 correlated with increased T- and B-cell infiltration and IFN expression. We show that intratumoral injection of a highly interferogenic TLR9 agonist, SD-101, in anti–PD-1 nonresponders led to a complete, durable rejection of essentially all injected tumors and a majority of uninjected, distant-site tumors. Therapeutic efficacy of the combination was also observed with the TSA mammary adenocarcinoma and MCA38 colon carcinoma tumor models that show little response to PD-1 blockade alone. Intratumoral SD-101 substantially increased leukocyte infiltration and IFN-regulated gene expression, and its activity was dependent on CD8⁺ T cells and type I IFN signaling. Anti–PD-1 plus intratumoral SD-101 promoted infiltration of activated, proliferating CD8⁺ T cells and led to a synergistic increase in total and tumor antigen-specific CD8⁺ T cells expressing both IFN-γ and TNF-α. Additionally, PD-1 blockade could alter the CpG-mediated differentiation of tumor-specific CD8⁺ T cells into CD127lowKLRG1high short-lived effector cells, preferentially expanding the CD127highKLRG1low long-lived memory precursors. Tumor control and intratumoral T-cell proliferation in response to the combined treatment is independent of T-cell trafficking from secondary lymphoid organs. These findings suggest that a CpG oligonucleotide given intratumorally may increase the response of cancer patients to PD-1 blockade, increasing the quantity and the quality of tumor-specific CD8⁺ T cells.